PRINCIPLES AND REQUIREMENTS FOR THE TRANSLATION PROCESS - Zakirova Dilrabo Haidarovna (Western European Studies, 2024)
The articletalks about the theory of translation, about the creation of a the oreticalmodel of translation, whichshowed the generalconcepts of equivalenceand the basis of the origin of translation. Intranslation, throughoutitshistory, there have been a largenumber of attempts to createcertaingeneralizationsandrules of translation. Allthiswas usuallypresentedin the form of principlesandrequirementsfor the translationprocess. Theprinciples were formed based on the translator's practiceandincludedrepetitiveaspects of practiceand were notbasedonanytheoreticalmodel of translation.
Keywords: equivalence; empiricalrules; transformation; linguistics